Performance Analysis of R600a as a Replacement for R134a in a Household Refrigeration System - Sudarma, Andi Firdaus; Carles, Henry; Azhar, Azmi; Akmal, Muhammad; Sirait, Alfa Firdaus (Universitas Mercu Buana, 2025)
This study evaluates the performance of a 50-liter mini refrigerator using R600a as an alternative to the factory-default refrigerant, R134a. The experimental setup included pressure gauges and digital thermometers to measure key parameters such as temperature and pressure at critical points in the refrigeration cycle. Tests were conducted under two scenarios: no-load and a 4 kg chicken meat load. Initially, the system operated with R134a at 16 bar and 20 g charge before being evacuated and recharged with R600a at the same pressure. Data was collected over a 10-minute period under stable conditions and analyzed using a P-h (Pressure-Enthalpy) diagram to determine enthalpy, refrigeration effect, compressor work, and coefficient of performance (COP). The effect of using R600a, efficiency increased 4% without load and 7% with load operation compared to R134a system. While COP actual has increased 5% and 10% respectively. The results indicate that R600a offers comparable performance to R134a while presenting potential advantages in terms of energy efficiency and environmental impact. These findings contribute to the ongoing evaluation of R600a as a sustainable replacement for R134a in household refrigeration applications.